Fabrication and Characterization of Copper System Compound Semiconductor Solar Cells. (29th July 2010) - Motoyoshi, Ryosuke; Oku, Takeo; Suzuki, Atsushi; Kikuchi, Kenji; Kikuchi, Shiomi; Jeyadevan, Balachandran; Cuya, Jhon
Abstract : Copper system compound semiconductor solar cells were produced by a spin-coating method, and their cell performance and structures were investigated. Copper indium disulfide- (CIS-) based solar cells with titanium dioxide (TiO 2 ) were produced on F-dopedSnO 2 (FTO). A device based on an FTO/CIS/TiO 2 structure provided better cell performance compared to that based on FTO/TiO 2 /CIS structure. Cupric oxide- (CuO-) and cuprous oxide- (Cu 2 O -) based solar cells with fullerene (C 60 ) were also fabricated on FTO and indium tin oxide (ITO). The microstructure and cell performance of the CuO/C 60 heterojunction and theCu 2 O :C 60 bulk heterojunction structure were investigated. The photovoltaic devices based on FTO/CuO/C 60 and ITO/Cu 2 O :C 60 structures provided short-circuit current density of 0.015 mAcm − 2 and 0.11 mAcm − 2, and open-circuit voltage of 0.045 V and 0.17 V under an Air Mass 1.5 illumination, respectively. The microstructures of the active layers were examined by X-ray diffraction and transmission electron microscopy.